Consumer Loyalty at Karaoke Party Events - Putri, Nabila; Fadhila, Rheza Yapi; Khumayah, Siti; Erawati, Dedet (ann4publisher@gmail.com, 2025)
This study aims to examine consumer loyalty at the “Weekend Party” Karaoke Event held at Kael Cavity Café in Cirebon City. The focus of this research is to understand the factors influencing consumer loyalty in karaoke party events, such as event quality, social interaction, and personalization of experiences during the event. Using a descriptive qualitative approach, data were collected through field observations, in-depth interviews with participants, organizers, and the venue owner. The study employs the theoretical framework of customer relationship management (CRM) to identify the key elements that contribute to consumer loyalty. The findings reveal that personalized experiences, active engagement between participants and organizers, and a deep understanding of audience preferences play a crucial role in fostering loyalty. Furthermore, the emotional attachment formed during the event significantly contributes to consumer loyalty, as reflected in their interest in attending future events and sharing positive experiences with others. The Karaoke Party event successfully enhanced customer lifetime value (CLV) through strategies that responded to participants’ needs, resulting in high satisfaction and long-term consumer loyalty.